Reduced thrombogenicity of surface-treated Nitinol implants steered by altered protein adsorption. (1st January 2022) - Gegenschatz-Schmid, Katharina; Buzzi, Stefano; Grossmann, Jonas; Roschitzki, Bernd; Urbanet, Riccardo; Heuberger, Roman; Glück, Dorothea; Zucker, Arik; Ehrbar, Martin
Abstract : Blood-contacting medical implants made of Nitinol and other titanium alloys, such as neurovascular flow diverters and peripheral stents, have the disadvantage of being highly thrombogenic. This makes the use of systemic (dual) anti-platelet/anticoagulant therapies inevitable with related risks of device thrombosis, bleeding and other complications. Meeting the urgent clinical demand for a less thrombogenic Nitinol surface, we describe here a simple treatment of standard, commercially available Nitinol that renders its surface ultra-hydrophilic and functionalized with phosphate ions. The efficacy of this treatment was assessed by comparing standard and surface-treated Nitinol disks and braids, equivalent to flow diverters. Static and dynamic (Chandler loop) blood incubation tests showed a drastic reduction of thrombus formation on treated devices. Surface chemistry and proteomic analysis indicated a key role of phosphate and calcium ions in steering blood protein adsorption and avoiding coagulation cascade activation and platelet adhesion. A good endothelialization of the surface confirmed the biocompatibility of the treated surface. Statement of significance: Titanium alloys such as Nitinol are biocompatible and show favorable mechanical properties, which led to their widespread use in medical implants. However, in contact with blood their surface triggers the activation of the intrinsic coagulation cascade, which may result in catastrophic thrombotic events. The presented results showed that a phosphate functionalization of the titanium oxide surface suppresses the activation of both coagulation cascade and platelets, avoiding the subsequent formation of a blood clot. This novel approach has therefore a great potential for mitigating the risks associated to either thrombosis or bleeding complications (due to systemic anticoagulation) in patients with cardiovascular implants. Graphical abstract: Image, graphical abstract